A study on Tumor Marker Calcitonin (CT) in Thyroid Patients - Alezzi, Buthaina I. H.; Al-Alassaf, Anwar I. S.; Al-Mageed, Nahla G. Abdul (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2012)
The study included 60 patients with preoperative single and multiple nodule goiter, their age ranged from (20-60) years. The other group included (20) persons as healthy control with age (20-60) years. Serum samples were tested by using ELISA technique for detection of (CT). Our findings indicated that calcitonin concentration in three patients with multiple nodule goiter had high mean level (20.69±3.55) compared with the other patients (4.18± 0.07). The detection of calcitonin concentration may the first studied descriptive study in Iraq, and the results were compared abroad studies. Lastly the level of thyroid hormone was not affected by the elevated concentration calcitonin